Feminism Discourse in Balance Ton Quoi (Linguistically Van Dijk Frame) - Sofiani, Yulia; Somba, Sugianti; Ramadhianti, Agustina (STKIP PGRI Tulungagung, 2024)
Ballance Ton Quoi is a French song that the researchers plan to analyze. This song is performed by Angèle. This song has attracted the attention of researchers, since it is impossible to discuss women without mentioning the social structures in which they exist. The purpose of the present research is to illustrate how critical discourse can reveal a text's hidden meaning. Aside from that, this study aims to demonstrate how social construction influences the perception of good and terrible women. Van Dijk's critical discourse analysis is used in the present research to analyze data. By examining and explaining the macro structure, super structure, and micro structure, the researchers seek to identify the implied meaning of this song. The present research adopts a descriptive qualitative method, with significant concepts highlighted and translated. According to the research's findings, the speaker believes that women should be able to value and respect who they are by not cheaply dressing or performing.